Descending Necrotising Mediastinitis: A Case Report Illustrating a Trend in Conservative Management - B. A. P. Jayasekera; O. T. Dale; R. C. Corbridge (Case Reports in Otolaryngology)
The mortality rate from descending necrotising mediastinitis (DNM) has declined since its first description in 1938. The decline in mortality has been attributed to earlier diagnosis by way of contrast-enhanced computed tomographic (CT) scanning and aggressive surgical intervention in the form of transthoracic drainage. We describe a case of DNM with involvement of anterior and posterior mediastinum down to the diaphragm, managed by cervicotomy and transverse cervical drainage with placement of corrugated drains and a pleural chest drain, with a delayed mediastinoscopy and mediastinal drain placement. We advocate a conservative approach with limited debridement and emphasis on drainage of infection in line with published case series.